If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + 8 = -4y + 9 Reorder the terms: 8 + -3y = -4y + 9 Reorder the terms: 8 + -3y = 9 + -4y Solving 8 + -3y = 9 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 8 + -3y + 4y = 9 + -4y + 4y Combine like terms: -3y + 4y = 1y 8 + 1y = 9 + -4y + 4y Combine like terms: -4y + 4y = 0 8 + 1y = 9 + 0 8 + 1y = 9 Add '-8' to each side of the equation. 8 + -8 + 1y = 9 + -8 Combine like terms: 8 + -8 = 0 0 + 1y = 9 + -8 1y = 9 + -8 Combine like terms: 9 + -8 = 1 1y = 1 Divide each side by '1'. y = 1 Simplifying y = 1
| 5d+3d= | | 8(x+5)=2(4x+4)+32 | | y=3(-9)+6 | | 10+-2y=12 | | 3/5-8=4 | | x^2+5/2x+25/16 | | f(x)=x^2+4x+9 | | 4s-10=18 | | 3x+2(3x+8)=16 | | -8+5x=-8+7x | | -16x^2+80x+3200=0 | | x/3-5=6 | | x/6+6=8 | | 2(5)-6y=7 | | 3/8x-1/3x=1/12 | | 203/2-403/4 | | -(3y+1)-(-2y-7)=1 | | 5(2)-2y=12 | | 5y+1=3 | | 2(x-4)-4(x-2)=x+2-(x-8) | | 18=x/3+3 | | -6y+2=0 | | m-17=-43 | | 51x=378.55 | | v^2-3v-40/4v^2-24v-64 | | =(4x+3)-(2x-4) | | (7/6x)-(14/9x) | | 5n+3=2n+12 | | (v^2-3v-40)/(4v^2-24v-64) | | 110-(-50)= | | (v^-3v-40)/(4v^-24v-64) | | 7/6x-14/9x |